Courtship Is a Major Factor of Mating‐Shortened Male Lifespan in an Egg Parasitoid - Zi‐Yin Wang; Jing Li; Jia‐Min Tang; Lan‐Feng Qiu; Hao‐Yuan Hu; Peng‐Cheng Liu (Ecology and Evolution)
ABSTRACT Mating is essential for population reproduction and survival, but individuals often incur costs of mating, including energy consumption and increased risks of death, predation, or disease transmission. Many studies on insects have reported a decreased post‐mating lifespan, and studies on the effects of mating on longevity have focused mainly on females. However, the effect of mating on lifespan has also been observed in males, and this process is thought to be more complex and distinctive. Sperm production and sperm transfer during copulation are believed to be the main factors involved in the mating‐induced reduction in male longevity due to significant energy investment, and this theory has been widely demonstrated in many insect species. Here, we found that mating has a negative effect on the longevity of males in an egg parasitoid species, Anastatus disparis. However, our results suggest that courtship rather than ejaculation is the main factor responsible for the reduced longevity of mated A. disparis males. Integrated transcriptomic analyses revealed the lots of upregulated genes and enriched Gene Ontology (GO) terms involved in lipid metabolism during male courtship. This finding suggested that lipid metabolism may be an important source of high energy expenditure during courtship. Besides, we discussed the role of increased lipid consumption for satisfying energy expenditure for courtship in the shortened lifespan of A. disparis males. In summary, our study provides comprehensive insights into post‐mating changes in male longevity and provides a basis for future mechanistic studies.